Effect of SWPBIS on Disciplinary Exclusions for Students With and Without Disabilities. (October 2019) - Grasley-Boy, Nicolette M.; Gage, Nicholas A.; Lombardo, Michael
School leaders react to inappropriate behaviors by excluding students, despite research suggesting an association with poor student outcomes. Students with disabilities are frequently subjected to these practices. One framework that has been proposed to reduce the reliance on reactive discipline procedures is schoolwide positive behavior interventions and supports (SWPBIS). In this study, we replicated several state-level quasi-experimental studies with discipline data from California. Using propensity score matching, we compared 544 schools implementing SWPBIS with fidelity and 544 schools that had never been trained. We found statistically significantly fewer out-of-school suspensions and days missed due to out-of-school suspensions across all students. Students with disabilities were statistically significantly less likely to be sent to alternative settings due to behavior in schools implementing SWPBIS with fidelity, with an effect size of −0.65. These results replicate and extend prior findings.